2016
DOI: 10.4238/gmr.15038402
|View full text |Cite
|
Sign up to set email alerts
|

In silico comparative analysis of tylenchid nematode pectate lyases

Abstract: ABSTRACT. Phytoparasitic nematodes can infect a wide range of crop plants, and cause billions of dollars of agricultural losses each year. These parasites represent the largest source of biotic stress experienced by plants. The order Tylenchida comprises the most important parasitic nematodes, particularly the root-knot and cyst nematodes. These parasitic organisms obtain nutrients to support their development through complex interactions with their hosts. Plant-parasitic nematodes secrete a mixture of cell-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Many studies have shown that pel is an important factor affecting host range. Different types of PELs recognise different sequences of methylated and unmethylated galacturonate sites with different chemical and enzyme properties (Herron et al 2000;Filho et al 2016), which may result in different pathogen host ranges. In this study, five pels from R. similis were screened and cloned based on R. similis transcriptome data, four of which belonged to the Class III family .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that pel is an important factor affecting host range. Different types of PELs recognise different sequences of methylated and unmethylated galacturonate sites with different chemical and enzyme properties (Herron et al 2000;Filho et al 2016), which may result in different pathogen host ranges. In this study, five pels from R. similis were screened and cloned based on R. similis transcriptome data, four of which belonged to the Class III family .…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic microorganisms destroy plant cell walls to facilitate their invasion via secreting PEL to degrade pectin and stimulate plant immune responses (Shevchik et al 1998;Ferrari et al 2013). Therefore, PEL plays an important role in the interaction between plant pathogens and their hosts and is an important factor affecting the host range of pathogens (Filho et al 2016). Currently, plant-parasitic nematodes are the only animals known to produce PEL.…”
Section: Introductionmentioning
confidence: 99%
“…Another in silico comparative analysis study showed that the legume lectin sequences ranged from 700 to 900 bp. Hundreds of structures of plant lectins have been characterized, and legume lectins are the most extensively studied (Moraes Filho et al, 2017).…”
Section: In Silico Characterization Of Plant Lectin Genesmentioning
confidence: 99%